Multiple modes of a natural circulation evaporator - Baars, Albert; Delgado, Antonio (International Journal of Heat and Mass Transfer, 2006)
The system behaviour of an open single tube, steam heated natural circulation evaporator has been investigated at heating steam pressures up to 0.44 MPa and different subcoolings of the process medium water. In the studied range of parameters, diverse operational states occurred which have been recognized for the first time as geysering coupled with manometer oscillation as well as first, second and third orders of density wave oscillation of type I. Due to the strong nonlinear behaviour of the system, up to three states appear in certain ranges of parameter constellations. By defined setting of initial conditions and distinct perturbations of the system, the individual states can be set. © 2006 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.tech.ITC.stmmec.multip
Keywords: Density wave oscillation; Geysering; Multiple modes; Natural circulation evaporator